(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Depression is a prevalent mental health issue among caregivers, especially those caring for patients with chronic conditions or requiring prolonged hospitalization. Early identification and intervention are crucial to improving both caregiver well-being and patient care quality. Objective: To determine the prevalence of depression and identify associated factors among caregivers of inpatients at the Medical and Pharmaceutical University Hospital. Methods: A cross-sectional study was conducted on 330 caregivers of inpatients at the Medical and Pharmaceutical University Hospital from December 2025 to March 2026. Depression was screened using the Patient Health Questionnaire-9 (PHQ-9) scale. Data were analyzed using descriptive statistics and multivariable logistic regression. Results: The prevalence of depressive symptoms among caregivers was 51.2%, including at-risk (22.7%), mild (9.7%), moderate (9.7%), and severe (9.1%) levels. The mean depression score was 7.5±7.2 (total: 27). Multivariable logistic regression identified several associated factors with depression as residing in rural areas (OR = 3.54; 95% CI: 1.54–8.09; p < 0.05); poor caregiver health status (OR = 2.23; 95% CI: 1.05–4.72; p = 0.036); caregiving burden (OR = 1.97; 95% CI: 1.09–3.56; p = 0.023). The type of patient illnesses was significantly associated with the depression of caregivers (p<0.001). Conclusion: More than half of the caregivers experienced depressive symptoms. Targeted psychological support, health education, and social assistance, particularly for older caregivers and those from rural areas, are essential to mitigate depression and enhance caregiving outcomes.